치매환자의 행동심리증상에 비약물적 중재가 미치는 효과 - 메타분석 - 권미화(Mi-Hwa Kwon); 이재신(Jae-Shin Lee) (한국콘텐츠학회 논문지, 17(6), 2017)
To investigate a variety of nonpharmacologic interventions have confirmed what the symptoms and effects, mainly interventions by acting on behavioral and psychological symptoms of dementia was conducted a meta-analysis. Data were collected from online search engines using search words from domestic and foreign article database. The researcher independently and among the pre-post experimental studies published from January 2000 to June 2016, recalled applying for the elderly with dementia presents the effect of treatment group and the control group RCT in this study were included in the study. The results of this meta-analysis showed that, effect size of the nonpharmacologic interventions of total -0.33, occupational therapy - 0.26, multi-sensory stimulation intervention -0.65 was significant beneficial effects to elderly with dementia(p<.05). According to interventions as a major affected the symptoms associated with behavioral problems, mainly aggression, memory-related problem behavior in the home-based program. Also, reminiscence therapy and occupational therapy is generally apathy, multi-sensory stimulation and music therapy was confirmed that there was a major change in behavior anxiety or agitation. The results of this study confirmed that various nonpharmacologic interventions were effective on behavioral psychological symptoms of dementia patients and confirmed the main symptoms of intervention. 본 연구는 치매환자의 행동심리증상에 미치는 다양한 비약물적 중재의 효과를 확인하고, 중재 별로 주요하게 작용된 증상이 무엇인지를 알아보고자 메타분석을 실시하였다. 자료 수집은 국 내외 검색엔진을 이용하였으며, 2000년 1월부터 2016년 6월까지 출판된 연구를 대상으로 하였다. 치매환자에게 적용한 비약물적 중재의 효과를 제시한 사전-사후실험연구 가운데 실험군과 대조군이 있는 무작위통제실험연구(Randomized Controlled Trial; RCT)를 대상으로 하였다. 최종 선정된 23편의 연구를 분석한 결과, 치매환자에게 적용한 다양한 비약물적 중재 연구 전체의 효과크기는 -0.33으로 "보통"의 효과크기가 나타났다. 세부적인 비약물적 중재 별 효과크기는 작업치료가 -0.26로 "보통"의 효과크기, 다감각자극이 -0.65로 "보통이상"의 효과크기로 임상적으로 유의한 차이가 있음이 증명되었다(p<.05). 중재 별로 주요하게 작용된 행동심리증상으로는 가정기반 프로그램에서는 주로 공격성, 기억력과 관련된 문제행동에 영향을 주었다. 또한, 회상치료와 작업치료는 대체적으로 무감정, 다감각자극과 음악치료는 불안이나 초조행동에 주요 변화가 있었음을 확인할 수 있었다. 본 연구 결과를 통하여 다양한 비약물적 중재가 치매환자의 행동심리증상에 효과가 있음을 확인할 수 있었으며, 중재 별로 주요하게 작용된 증상을 확인 할 수 있었다. 따라서 추후 임상에서 치매환자를 위한 비약물적 중재 시, 각 환자의 행동심리증상에 적합한 중재를 선택하여 접근하는 노력이 필요 할 것이다.